2015
DOI: 10.1021/acs.energyfuels.5b00269
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonswelling Clay Minerals (Illite, Kaolinite, and Chlorite) on Nonaqueous Solvent Extraction of Bitumen

Abstract: Artificial mixtures of bitumen with three natural clay standards, dominated by illite, kaolinite, and chlorite, were reacted for several days and washed three times each with cyclohexane to remove bitumen from the clays. The main goal was to determine and better understand the effect of nonswelling clay minerals (illite, kaolinite, and chlorite) on nonaqueous solvent bitumen extraction. The experimental results showed that the total amount of residual cyclohexane insoluble organic carbon (CIOC) measured for cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 30 publications
3
56
0
Order By: Relevance
“…Several studies have reported that the presence of organic matter in the rocks may influence the analytical methods for measuring surface properties . Although many studies have revealed that organic matter positively affects the results of SSA‐BET from soil, high amounts of organic carbon lowers SSA‐BET results due to larger aggregates forming from smaller particles by attaching to organic matter and/or blocking up holes with sticky organic carbon . Therefore, in the present study, the Dean‐Stark extraction procedure was performed on all petrologic end‐members to remove bitumen to prevent the influence of bitumen on surface properties.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the presence of organic matter in the rocks may influence the analytical methods for measuring surface properties . Although many studies have revealed that organic matter positively affects the results of SSA‐BET from soil, high amounts of organic carbon lowers SSA‐BET results due to larger aggregates forming from smaller particles by attaching to organic matter and/or blocking up holes with sticky organic carbon . Therefore, in the present study, the Dean‐Stark extraction procedure was performed on all petrologic end‐members to remove bitumen to prevent the influence of bitumen on surface properties.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, out of two samples collected from the Tofield and Athabasca areas, one contained half as much Rb as the other one. It is known that Rb has good bioaccumulation properties, and it is abundant in the areas rich in granite or illite clays, which have been reported as the main clay types in Alberta [44]. Due to there being only a few studies conducted on the Rb impact on human health, there is currently no RDI established for this element [45].…”
Section: Discussionmentioning
confidence: 99%
“…In 1929, Dr. Clark established a model plant to extract the oil using hot water and a chemical agent, and by 1969, the hot water extraction (HWE) process was commercially applied for the shallow oil sands deposits. It was found that the surface of minerals was typically surrounded by a thin film of connate water, which could facilitate the liberation of bitumen from the oil sands ore during the HWE (Hooshiar et al 2012;Osacky et al 2015). However, high consumption of freshwater and fast accumulation of toxic and slow setting mature fine tailings inherent to the HWE process have raised growing public concerns about the environmental and ecological sustainability of the oil sands processing.…”
Section: Introductionmentioning
confidence: 99%